Discovery of novel antimicrobial peptides, Brevilaterin V, from Brevibacillus laterosporus S62-9 after regulated by exogenously-added L-valine. (1st February 2022) - Chen, Zhou; Wang, Xingxing; Han, Panpan; Liu, Yangliu; Hong, Dan; Li, Siting; Ma, Aijin; Jia, Yingmin
Abstract: Properties of short-chain antimicrobial peptides (AMPs) depend on their primary structures. Brevibacillus laterosporus was previously found to secrete five AMPs. Herein, we discovered exogenously-added l -valine could regulate this strain to produce novel AMPs (named as Brevilaterin V) with new primary structures. Five novel Brevilaterins V with linear peptides were purified and characterized. They had high antimicrobial activities against 10 tested pathogenic bacteria. Brevilaterins V exhibited a good stability even treatment at 100 °C, or pH 2 or pH 12, for 2 h. Interestingly, all novel Brevilaterins V showed low hemolytic activities. In particular, the hemolytic rates of Brevilaterin V1 and Brevilaterin V2 were <5%; however, single changes in primary structure or a single extra methylene in the N -terminal fatty acid chain increase the hemolytic activity. The strategy of using amino acids in culture medium to regulate AMPs production by Br. laterosporus provides a basis for improvement of the range and properties of known AMPs. Highlights: l -Valine regulates Brevibacillus laterosporus to produce new antimicrobial peptides. This regulation strategy is the first report for improving the properties of AMPs. New found AMPs exhibit high antibacterial activities but low hemolytic activities.